2006
DOI: 10.1897/06-017r.1
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of phase distribution of pyrethroid insecticides in sediment

Abstract: Synthetic pyrethroids are strongly hydrophobic compounds, and their toxicity in sediment is regulated by phase distribution among the sediment, dissolved organic matter, and water phases. In the present study, we spiked and equilibrated four pyrethroids in two sediments, and we characterized their phase distribution as a function of contact time. The freely dissolved concentration measured by solid-phase microextraction was only a small fraction (<16.3%) of the total pore-water concentration as determined by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Previous research has shown that contaminants in an ambient water sample are distributed into three distinct phases: solid adsorbed, dissolved organic carbon adsorbed, and freely dissolved (Liu et al 2004). The freely dissolved fraction of most hydrophobic contaminants ranges from 1 to 27 %, and typically this number decreases over time (Liu et al 2004;Bondarenko et al 2006). In our study we estimated the dissolved esfenvalerate fraction to range from 0.4 to 22.7 % after only 12 h, decreasing with increasing algal concentration, which is consistent with previous findings (Liu et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown that contaminants in an ambient water sample are distributed into three distinct phases: solid adsorbed, dissolved organic carbon adsorbed, and freely dissolved (Liu et al 2004). The freely dissolved fraction of most hydrophobic contaminants ranges from 1 to 27 %, and typically this number decreases over time (Liu et al 2004;Bondarenko et al 2006). In our study we estimated the dissolved esfenvalerate fraction to range from 0.4 to 22.7 % after only 12 h, decreasing with increasing algal concentration, which is consistent with previous findings (Liu et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…The spatial pattern of fipronil contamination also coincided with pyrethroids, with the highest P FIP occurring at correlated with sediment fines (R s ¼ 0.79; p < 0.01; n ¼ 12), but was not correlated with TOC (R s ¼ 0.31; p < 0.2; n ¼ 18). In the absence of usage data to assess occurrence and persistence, the lower hydrophobicity and sediment-water partition coefficients for fipronil and its degradates compared with pyrethroids [32][33][34] can explain these trends.…”
Section: Fipronil and Its Degradatesmentioning
confidence: 99%
“…Pyrethroids have high affinity for organic carbon and very low solubility in water and volatility to the atmosphere, which makes them less environmentally mobile and harmful pesticides (Brady et al, 2006), although Werner et al (2004), have noticed that they may be highly toxic to fish larvae. Their distribution in the water column is mainly to the sediment compartment and dissolved organic carbon (Spurlock et al, 2005), although the time dependence of phase distribution is an important factor (Bondarenko et al, 2006). Yang et al (2006), observe a significant impact of suspended sediments on the bioavailability of pyrethroids in the water column.…”
Section: Pyrethroids Usage and Propertiesmentioning
confidence: 99%